The yield of eggplant depending on climate conditions and mulching - Adamczewska-Sowińska Katarzyna; Krygier Magdalena; Turczuk Joanna (Folia Horticulturae, 2016)
The field production of eggplant in moderate climates is difficult as it depends heavily on thermal conditions. Eggplant is a species that is sensitive to low temperatures, and temperatures below 16°C constrain the growth of young plants. Other disadvantageous factors include: temperatures that are too high, water shortage and excessive soil humidity. The growth conditions for eggplant can be improved by using mulches. The purpose of the experiment was the assessment of eggplant cropping while using synthetic mulches of polyethylene foil and polypropylene textile. The research took five years (2008-2012) and on the basis of the obtained results it was possible to determine the influence of weather conditions on the yielding of this species. It was proven that eggplant cropping significantly depended on the air temperature and the amount of rainfall during the vegetation period. The highest yield was observed when the average air temperature was high and at the same time rainfall was evenly distributed throughout the vegetation season. It also turned out that the agro-technical procedure which significantly increased eggplant fruit cropping was mulching the soil with polyethylene black foil, or transparent foil, previously having applied a herbicide.